2018
DOI: 10.1590/1809-4392201700602
|View full text |Cite
|
Sign up to set email alerts
|

Silvicultural performance of five forest species in the central Brazilian Amazon

Abstract: Planting of forest species of timber interest helps to reduce the deforestation pressure on the Amazon forest, promotes sustainable development of the producing region and generates ecological benefits. The objective of this work was to evaluate the survival rate and growth of four native (Swietenia macrophylla, Parkia decussata, Dipteryx odorata and Jacaranda copaia) and one exotic (Acacia mangium) species in monospecific plantations (spacing of 2 x 2 m) established on areas previously used for grazing, in It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Tree plantations have the potential to produce large quantities of timber on relatively small areas: timber plantations in Brazil, mostly fast-growing eucalyptus and pine, can produce 200-400 m 3 ha −1 of roundwood on 10-15 year cycles [65]. Such exotic species produce low-grade timber that is not directly equivalent to high-value wood currently extracted from Amazonian natural forests, but there is a potential to develop plantations of high-value native species [66,67], even though technical alternatives are still scarce in Amazonia [67]. Moreover, it is likely that with ongoing technological advances, future high-grade timber demand will be gradually substituted by less-valuable fast-growing timbers transformed into highlyresistant materials [68].…”
Section: Future Timber Production In Integrated Forest Landscapesmentioning
confidence: 99%
“…Tree plantations have the potential to produce large quantities of timber on relatively small areas: timber plantations in Brazil, mostly fast-growing eucalyptus and pine, can produce 200-400 m 3 ha −1 of roundwood on 10-15 year cycles [65]. Such exotic species produce low-grade timber that is not directly equivalent to high-value wood currently extracted from Amazonian natural forests, but there is a potential to develop plantations of high-value native species [66,67], even though technical alternatives are still scarce in Amazonia [67]. Moreover, it is likely that with ongoing technological advances, future high-grade timber demand will be gradually substituted by less-valuable fast-growing timbers transformed into highlyresistant materials [68].…”
Section: Future Timber Production In Integrated Forest Landscapesmentioning
confidence: 99%
“…Monospecific plantations of four native species (Dipteryx odorata, Jacaranda copaia, Parkia decussata, and Swietenia macrophylla) and the exotic A. mangium established to restore pasture areas, have shown a decline in silvicultural performance e.g., biometric data, crown projection area, total height, commercial cylinder volume etc. of A. mangium compared to other species (Machado et al 2018). These authors did not recommend A. mangium for restoration because of its limited performance in relation to most of the variables that were assessed.…”
Section: Limitations Of a Mangium: From Benefits To Threatsmentioning
confidence: 98%
“…In turn, in a study on the silvicultural performance of five forest species (Dipteryx odorata, Parkia decussata, Jacaranda copaia, Acacia mangium and Swietenia macrophylla) in the Amazon rainforest in Brazil conducted by Machado et al (2018) the hierarchical cluster analysis showed that the species D. odorata and P. decusata showed similarities forming a group with a slightly lower similarity with J. copaia, these three species reported the greatest similarities in the diametric variables evaluated diameter at breast height, total height, crown projection area and volume of the commercial cylinder in this study. On the other hand, D. odorata, J. copaia and P. decussata showed less similarity with the other native species S. macrophylla.…”
Section: Cluster Analysismentioning
confidence: 99%